2004
DOI: 10.1113/jphysiol.2004.070359
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and molecular characterization of the inward rectifier in juxtaglomerular cells from rat kidney

Abstract: Renin, the key element of the renin-angiotensin-aldosterone system, is mainly produced by and stored in the juxtaglomerular cells in the kidney. These cells are situated in the media of the afferent arteriole close to the vessel pole and can transform into smooth muscle cells and vice versa. In this study, the electrophysiological properties and the molecular identity of the K + channels responsible for the resting membrane potential (∼ −60 mV) of the juxtaglomerular cells were examined. In order to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…In addition, the vessels were prepared from NaCl-depleted rats in order to maximise the number of renin-secreting cells (Taugner and Hackenthal 1989). We have indeed found that, the vast majority of cells that we observe under these conditions at the vessel pole are renin-positive (Leichtle et al 2004). In the more proximal parts of the afferent arteriole, however, smooth muscle cells predominate and the responses to stimulation by ISO + IBMX were compared in the two regions (distal: 0-20 μm, proximal: 60-100 μm from the entrance into the glomerulus).…”
Section: Regional Specificity Of the Ca 2+ Responsementioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the vessels were prepared from NaCl-depleted rats in order to maximise the number of renin-secreting cells (Taugner and Hackenthal 1989). We have indeed found that, the vast majority of cells that we observe under these conditions at the vessel pole are renin-positive (Leichtle et al 2004). In the more proximal parts of the afferent arteriole, however, smooth muscle cells predominate and the responses to stimulation by ISO + IBMX were compared in the two regions (distal: 0-20 μm, proximal: 60-100 μm from the entrance into the glomerulus).…”
Section: Regional Specificity Of the Ca 2+ Responsementioning
confidence: 99%
“…This is of importance, as the cells in this preparation are strongly coupled by gap junctions (Kurtz and Penner 1989;Russ et al 1999;Leichtle et al 2004). A disadvantage of the preparation is the absence of an intravascular pressure which results in a negative membrane potential (from -60 to -65 mV (Kurtz and Penner 1989;Leichtle et al 2004)) and low values of [Ca 2+ ] i (Laske-Ernst et al 2008). Furthermore, the afferent arteriole is composed of smooth muscle cells and JGC and, at least in principle, one cannot be certain from which cell type the signal arises.…”
Section: Isolated Afferent Arteriolesmentioning
confidence: 99%
See 3 more Smart Citations